Effectiveness of Relocating Street Merchant in The Batik Trusmi Area of Cirebon - Nadiya Fitri Nura’ini; Yanto Heryanto (CV. Media Digital Publikasi Indonesia, 2026)
The potential of the Trusmi Batik Tourism Area as a space is a problem of space management and traders are not properly organized, as a result the streets are often congested, the condition is chaotic, and the traders are very competitive. To solve this problem, the Cirebon Regency Government initiated a program of relocating traders in July 2025 based on Regional Regulation No 4 of 2021 on Public Order. Program effectiveness was evaluated by Campbell's Evaluation framework in five categories: program success, target accuracy, beneficiary satisfaction, input-output ratio, and goal achievement. In a descriptive type of qualitative strategy, purpose sampling including those from Planning Agency, Street Vendor Association, vendors and visitors. Data collection methods included interview, field observation and documentary review. The data were analyzed as the Miles and Huberman model together with triangulation. The outcomes seem to indicate that the program has been quite successful. Vendor compliance is very high, sales overhead and traffic flow are positively affected, and the community responses are fairly positive. Success has been achieved by planning well, establishing good interagency working relationships and forums for debate, choosing an apposite location in the tourism system, setting up a joint funding scheme and involving community organizations. Despite all these difficulties, there are still some problems being overlooked such as the shortage of weather stations, the potential of future management capacity improvement, and the program framework depending too much on some people. These problems need some more long-term approaches for sustainability.